Talking God : Leaphorn & Chee #9 - Hillerman, Tony (New York : Harper & Row, 1989)
While investigating what is supposed to be a case of grave robbing, tribal police learn there's more, much more, involved.
Keywords: Leaphorn, Joe, Lt. (Fictitious character) -- Fiction; Chee, Jim (Fictitious character) -- Fiction; Police -- Southwestern States -- Fiction; Navajo Indians -- Fiction